Raman Spectroscopy Detects Changes in Carotenoids on the Surface of Watermelon Fruits During Maturation - Dhanani, Tushar; Dou, Tianyi; Biradar, Kishan; Jifon, John; Kurouski, Dmitry; Patil, Bhimanagouda S. (Frontiers in Plant Science, 2022)
A non-invasive and non-destructive technique, Raman spectroscopy, was explored to distinguish different maturity stages (20, 30, 40, and 50 days after anthesis) of watermelon (Citrullus lanatus) fruits from four cultivars: Fascination, Orange Crisp, Amarillo and Crimson Sweet. Spectral acquisition from the fruit surface was carried out at the wavelength range of 400-2000 cm-1 using a handheld Raman spectrometer equipped with 830 nm laser excitation source. The spectra were normalized at 1438 cm-1 which was assigned to CH2 and CH3 vibration. Detecting changes in the spectral features of carotenoids on the surface of watermelon fruits can be used as a marker to monitor the maturity of the fruit. The spectral analysis confirmed the presence of two major carotenoids, lutein and β-carotene and their intensity decreased upon maturity on the fruit surface. Identification of these pigments was further confirmed by resonance Raman spectra and high-performance liquid chromatography analysis. Results of partial least square discriminant analysis of pre-processed spectra have demonstrated that the method can successfully predict the maturity of watermelon samples with more than 85% accuracy. Analysis of Variance of individual Raman bands has revealed a significant difference among the stages as the level of carotenoids were declined during the ripening of the fruits. Thus, Raman spectral signatures can be used as a versatile tool for the non-invasive determination of carotenoid changes on the watermelon fruits' surface during ripening thereby enabling effective monitoring of nutritional quality and maturity indices before harvesting the watermelon.